Implications of prognostic pessimism in patients with chronic obstructive pulmonary disease (COPD) or asthma admitted to intensive care in the UK within the COPD and asthma outcome study (CAOS): multicentre observational cohort study. Issue 7630 (1st November 2007) - Wildman, Martin J; Sanderson, Colin; Groves, Jayne; Reeves, Barnaby C; Ayres, Jon; Harrison, David; Young, Duncan; Rowan, Kathy
Abstract : Objective To determine whether clinicians' prognoses in patients with severe acute exacerbations of obstructive lung disease admitted to intensive care match observed outcomes in terms of survival. Design Prospective cohort study. Setting 92 intensive care units and three respiratory high dependency units in the United Kingdom. Participants 832 patients aged 45 years and older with breathlessness, respiratory failure, or change in mental status because of an exacerbation of COPD, asthma, or a combination of the two. Main outcome measures Outcome predicted by clinicians. Observed survival at 180 days. Results 517 patients (62%) survived to 180 days. Clinicians' prognoses were pessimistic, with a mean predicted survival of 49% at 180 days. For the fifth of patients with the poorest prognosis according to the clinician, the predicted survival rate was 10% and the actual rate was 40%. Information from a database covering 74% of intensive care units in the UK suggested no material difference between units that participated and those that did not. Patients recruited were similar to those not recruited in the same units. Conclusions Because decisions on whether to admit patients with COPD or asthma to intensive care for intubation depend on clinicians' prognoses, some patients who might otherwise survive are probably being denied admission because of unwarranted prognostic pessimism.